Bulgaria : Financial Sector Assessment Program: Technical Note-Risk Assessment and Stress Test of the Banking System. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses results of risk assessment and stress tests (ST) of the banking system in Bulgaria. ST results reveal that the Bulgarian banking system is vulnerable to the extreme realization of internal and external risks coupled with the need to clean the balance sheets from nonperforming loans (NPLs). In the baseline scenario, characterized by a modest economic growth and decline in unemployment, as well as stable and low interest rates, two banks-including a systemic one-exhibit weakness in terms of capital buffers to cope with accumulated losses in the past. These banks also experience substantial increase in their NPLs as a result of the asset quality review adjustment.